2020
DOI: 10.1021/acs.jpcb.0c02401
|View full text |Cite
|
Sign up to set email alerts
|

Modification of AFLC Physical Properties by Doping with BaTiO3 Particles

Abstract: In this paper, for the first time, the influence of the BaTiO3 particles on the antiferroelectric liquid crystalline phase was shown. Low concentrations and two different sizes of BaTiO3 particles (nano- and submicroparticles) were used. It was found that admixture of the ferroelectric particles causes a decrease in the concentration of free ions in the liquid crystal matrix. Despite the small amount of admixture, a decrease in spontaneous polarization, switching time and rotational viscosity, was observed, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Finally, we would like to address Eqs. ( 3) and ( 4), which are often recalled when discussing dielectric spectra in the LF domain [32][33][34][35][36][37][38][39][40]. The above discussion validated Eq.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Finally, we would like to address Eqs. ( 3) and ( 4), which are often recalled when discussing dielectric spectra in the LF domain [32][33][34][35][36][37][38][39][40]. The above discussion validated Eq.…”
Section: Resultsmentioning
confidence: 58%
“…1. For discussing this behavior, two relations are explored in LC materials and their nanocomposites [32][33][34][35][36][37][38][39][40]:…”
Section: Introductionmentioning
confidence: 99%
“…30–50 nm), the nematic–isotropic liquid phase transition temperature increases by almost 40 °C, as well as an increase in dielectric and optical anisotropy is observed [ 13 ]. By doping antiferroelectric liquid crystal mixture with BaTiO 3 nanoparticles, we obtained faster molecular switching, a drop in threshold voltage and spontaneous polarization, as a result of modification of the local electric field [ 14 ]. In turn, Manepalli et al showed that the self-organization of ZnO nanoparticles (ca.…”
Section: Introductionmentioning
confidence: 99%
“…In 2a , which has a short fluoroalkyl moiety, no diffraction peak corresponding to the (001) plane index was observed ( Figure S18a ). It is considered that the fluorine atoms in the flexible chain formed an interdigitate structures, which formed many defects in the layer structure and reduced the domain size [ 24 , 25 ]. In contrast, 2b and 2c , which has an elongated fluoroalkyl structure, exhibited diffraction peaks corresponding to the (001) plane at 2 θ = 2.46° and 2.22°, respectively ( Figure 5 d and Figure S18e ).…”
Section: Resultsmentioning
confidence: 99%